Conceptualising Augmented Reality: From virtual divides to mediated dynamics. (June 2021) - Heemsbergen, Luke; Bowtell, Greg; Vincent, Jordan
Although Augmented Reality (AR) scholarship is largely defined through technocentric boundary work that delineates the virtual from the real, it is nevertheless vital to consider experiential conceptualisations of AR as mediating the human–physical environment, as this makes visible for analysis specific properties that afford specific dynamics of augmented publics. We consider how AR mediates the environment in ways previous media could not, identifying four affordances of note. We name visual (dis)integrity, environmental activation, contextual pointalisation and four-dimensional place(ment), as well as reliance on digital infrastructures as sets of properties and dynamics that speak to what AR affords its users. The article first traces how the conceptualisation of AR in scholarship has yet to move past technocentric metaphors of description, adopted from the Virtuality Continuum (Milgram et al., 1995) that separates reality from mediating technologies. It then pushes media critique conceptualising AR in ways that more accurately account for lived experiences of perception. Doing so updates the metaphors used to understand AR and exposes first- and second-order affordances of AR media, which define but are not definitive of the constraints and potentials present in how the properties and dynamics of AR mediate perceptions of life. The article concludes by noting how future research can now consider definitions of AR media that centre on how perceptible spatial computation augments relations between objects, whether these are conjured from electrons, atoms or humans.